PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR MATEMATIKA DI KELAS V SDN 04/II JAYA SETIA - Nurlev Avana Alwen Bentri Nurhizrah Gistituati (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
This type of research is Classroom Action Research (CAR) which is carried out in 4 stages of planning, implementation, observation and reflection with 2 learning cycles. The subjects in this study were the fifth grade students of elementary school 04/II Muara Bungo, totaling 27 students. Data collection techniques are observation, test and documentation. Based on the results of the study, it can be seen that the teaching process of educators increased by 77.50% in the first cycle, then increased to 87.49% in the second cycle and the students' mathematics learning process which was 29,46% in the first cycle to 75,92% in the second cycle. It also shows an increase in students' mathematics learning outcomes, namely 14 (51.85%) students who achieve the KKM in the first cycle increasing to 22 (81.48%) who reach the KKM in the second cycle, so it can be concluded that the Educational approach Indonesian Realistic Mathematics (PMRI) can improve the process and results of learning mathematics for students at grade V of elementary School 04/II Jaya Setia.